The effect of Corporate Social Responsibility (CSR) activities on company’s public reputation: a study on Chevron Bangladesh - Gomes, Sophia Shawon (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.